The Theoretical interpretation of revolutions: Evolution of concepts and diversity of questions - Idrees, Ihsan B F; Dr.Muhammad Saud; Asia Ashfaq (Journal of Peace, Development and Communication, 2021)
The revolution as a social, political, and even historical phenomenon also occupied a large part of theoretical interpretations in both political science, social science, economics, and sometimes psychology and anthropology. This paper seeks to simplify some of the theoretical concepts of revolutions, and the evolution in these concepts from one era to another. Besides, it explained the reasons for the revolutions, as well as explaining the role of the actors in it, and trying to clarify the reasons that led to the diversity of theories.